Novejše metode proučevanja dramskega teksta in uprizoritve - Žakelj, Špela (Primerjalna književnost, 2004)
A number of different methods can be used to analyze dramatic texts, structuralism and new historicism being two of them. Contrary to the method of new historicism, structuralism can include dimension of stage representation, while new historicism focuses only on text itself and tends to discover hidden features of the era in which the text was originally written. Methods of analyzing dramatic texts are better known than those that are used to analyze theatrical representations. Using semiotic method Patrice Pavis developed vectorisation as an independent procedure for analyzing theatrical representations, which doesn't focus only on verbal parts of representation, but also includes its figural dimensions. By applying procedures developed by modern methods on Shakespeare's tragedy Romeo and Juliet and on the case of its theatrical application by Dusan Jovanović, new dimensions of the text and its representation can be obtained.
Keywords: Shakespeare, William, 1564-1616; Jovanović, Dušan, 1939-; teorija drame; gledališka semiotika; dramsko besedilo; gledališka uprizoritev